2023
DOI: 10.1021/acs.jafc.3c04329
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the “Relative Ordered Structure of Hericium erinaceus Polysaccharide” from Different Origins: Based on Similarity and Dissimilarity

Shi-Kang Chen,
Yu-Hao Li,
Xin Wang
et al.

Abstract: Polysaccharides are organic compounds widely distributed in nature, but structural order and disorder remain a formidable problem. In this study, based on the theoretical framework of the "relative ordered structure of polysaccharide" proposed in our previous work, the structural order of Hericium erinaceus polysaccharides from different regions was evaluated by FT-IR, methylation analysis, and 1 H NMR spectroscopy combined with chemometric methods. The results of principal component analysis and heatmap clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…This result indicated that the purified fractions prepared under the same conditions had similar monosaccharide compositions. A similar phenomenon was also observed in the purified polysaccharides from Hericium erinaceus …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This result indicated that the purified fractions prepared under the same conditions had similar monosaccharide compositions. A similar phenomenon was also observed in the purified polysaccharides from Hericium erinaceus …”
Section: Resultssupporting
confidence: 81%
“…Similarly, H. erinaceus polysaccharides from different origins were composed of four polysaccharides structural types, including fucogalactoglucan, glucofucogalactan, fucoglucan, and glucan . The viewpoint also corresponded to the conserved properties of the basic physiological blueprint of the fungal cell wall architecture .…”
Section: Discussionmentioning
confidence: 99%